Application of Guided Inquiry Method to Developing Students' Creative Thinking Skills in Subjects Integrated Social Studies Class VIII-A UPTD SMP Negeri 1 Sirombu - Daeli, Trisna Dewinta Ester; Laoli, Eka Septianti; Harefa, Yearning; Lahagu, Arianto (Golden Ratio of Data in Summary, 2025)
This study is motivated by the results of observations of researchers during the implementation of the learning process at UPTD SMP Negeri 1 Sirombu in the 2023/2024 academic year which has experienced obstacles in the learning process so that students' thinking skills are still relatively low. This researcher aims to (1) Know the application of the Guided Inquiry Method can develop students' creative thinking skills in Integrated Social Studies Class VIII-A UPTD SMP Negeri 1 Sirombu 2023/2024. (2) Knowing the increase in student understanding after using the Guided Inquiry Method to Develop Students' Creative Thinking Skills in Integrated Social Studies Class VIII-A UPTD SMP Negeri 1 Sirombu Lesson Year 2023/2024. This type of research is class action research (PTK). This research was conducted in class VIII-A with 33 students. The instruments used were teacher and student observation sheets, interviews, and documentation. Based on the results known by researchers in the field, it is known that: (1) The results of observations for teachers in the first cycle activities reached an average of 59%, while in the second cycle activities the teacher's ability to implement the learning process increased from the previous results reaching 85%. (2) The results of student observations on student activities in the first cycle activities reached an average of 77.91% and in the second cycle increased to 92.38%. (3) The results of the learning evaluation in cycle I were 64.62%, and in cycle II experienced an increase from the results of the previous cycle which amounted to 81.03%, the percentage of completeness achieved in cycle I was 39.13%, while in cycle II it reached 95.65%. So it can be concluded that the application of the Guided Inquiry Method provides an increase and understanding of both the teacher and especially to students where students can predict, observe, and explain the results of their observations in the learning process that takes place in the classroom. the application of the Guided Inquiry Method can develop students' creative thinking skills in Integrated Social Studies Class VIII-A UPTD SMP Negeri 1 Sirombu Lesson Year 2023/2024.